2020
DOI: 10.1515/ijcre-2019-0201
|View full text |Cite
|
Sign up to set email alerts
|

Micro-emulsion synthesis of La1 − xCrxFeO3 nanoparticles: effect of Cr doping on ferroelectric, dielectric and photocatalytic properties

Abstract: In the present study, La1 − xCrxFeO3 (x = 0.0, 0.3, 0.6, 0.9, 1.0) was synthesized by micro-emulsion route and characterized by X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Scanning electron microscope (SEM), Energy-dispersive X-ray (EDX) techniques. The dielectric, ferroelectric and photocatalytic properties were investigated and compared with un-doped material. The XRD analysis revealed orthorhombic geometry of La1 − xCrxFeO3 (x = 0.0, 0.3, 0.6, 0.9, 1.0), Cr was doped successfully into the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Furthermore, Figure S10(c–d) reveals the higher dielectric loss 1.11E+04 and 1.24E+03 in the lower frequency zone at 393 K, whereas continuing the process at 303 K shows values of 8.41E+02 and 6.63E+02 in the higher frequency region. These dielectric behaviors can be distinguished at lower frequencies due to electron exchange that is harmonized with the applied electric field, whereas at higher frequencies, there is no appropriate time for electron orientation with the external electric field, resulting in shows constant dielectric response [58] . S. Han et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Figure S10(c–d) reveals the higher dielectric loss 1.11E+04 and 1.24E+03 in the lower frequency zone at 393 K, whereas continuing the process at 303 K shows values of 8.41E+02 and 6.63E+02 in the higher frequency region. These dielectric behaviors can be distinguished at lower frequencies due to electron exchange that is harmonized with the applied electric field, whereas at higher frequencies, there is no appropriate time for electron orientation with the external electric field, resulting in shows constant dielectric response [58] . S. Han et al.…”
Section: Resultsmentioning
confidence: 99%
“…These dielectric behaviors can be distinguished at lower frequencies due to electron exchange that is harmonized with the applied electric field, whereas at higher frequencies, there is no appropriate time for electron orientation with the external electric field, resulting in shows constant dielectric response. [58] S. Han et al found that a high dielectric constant expands solubility whereas a low dielectric constant increases ion transportation speed. [59] According to the obtained results, Li 2 TP has a low dielectric constant and dielectric loss than TPA is an added advantage for the high reversibility of their electrochemical process.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Moreover, variation in the sizes of A and B cation offers opportunity to modify the ABO 3 type materials by doping. The ABO 3 type perovskite materials exhibit excellent electrocatalytic, ionic and electronic conductivity, optical, mechanical, and magnetic properties 6‐9 . The LaNiO 3 type of perovskite (ceramics structured) possesses amazing applications in transducers, sensors, capacitors, random access memories, wireless communications, tunable microwave devices, and piezoelectric devices.…”
Section: Introductionmentioning
confidence: 99%